Genetic profiling and PVY resistance identification of potato germplasm resources - Gao, Yan; Tian, Chenxi; Du, Yizhi; Zhao, Yong; Jiang, Rui; Zhang, Kai; Lv, Dianqiu (Frontiers in Plant Science, 2024)
Excellent germplasm resources are the foundation for cultivating high-quality, disease-resistant, and stress-tolerant varieties. In this study, simple sequence repeat (SSR) markers were used to identify 138 potato accessions collected from worldwide, and genetic cluster analysis was used to characterize the genetic diversity of the tested germplasm resources. The Potato virus Y (PVY) resistance of these potato accessions was identified by artificial friction inoculation combined with molecular marker detection, and potato accessions with different PVY resistance were screened based on disease index and incidence rate. Using SSR markers, 138 potato accessions were identified, and the results showed that the genetic distances between the tested potato germplasm resources ranged from 0.025 to 0.660, and the genetic similarity coefficients ranged from 0.489 to 0.975. The 138 accessions could be clustered into five subgroups using Unweighted Pair-Group Method with Arithmetic Mean (UPGMA). Among them, Z173, Biyin No. 4, Suyin No. 2, XN995, XN987, Biyin No 22, Bibiao104, Sarpo mira, XN996, XN979, Desiree, RUNSHI, Actrice, Jia 1219, Heyin No 12, and Moyin No.1 have relatively distant genetic relationship with another 122 accessions. Based on the disease index, the following different accessions were screened: five highly resistant, 11 resistant, 45 moderately resistant, 35 susceptible, and 42 highly susceptible. Fourteen resource materials with good resistance (disease index ≤ 33.74%, and a grading of high resistance (HR) or medium resistance (MR); incidence rate ≤ 67.58%) were identified. By combining genetic cluster analysis and PVY resistance identification, six accessions showed PVY resistance and had distant genetic relationships with other accessions selected which provided important materials for disease resistance breeding and quality improvement of potato. In this study, the genetic diversity and PVY resistance of global potato germplasm resources was explored, and potato germplasm materials with important utilization value were screened. The results obtained in this study could provide important references for the research and utilization of global potato germplasm resources.